INTERNALISASI NILAI-NILAI KEBHINEKAAN GLOBAL DALAM HARMONI KEHIDUPAN DINASTI SANJAYA DAN DINASTI SYAILENDRA PADA MASA KERAJAAN MATARAM KUNO UNTUK MENYONGSONG PEMBELAJARAN SEJARAH ABAD 21 - Dewi, Candra Ulfa Kusuma; Septaningtyas, Khairunisa Hening; Shary, Linggar Charista; Nugroho, Aditya Widiadi (Universitas Negeri Malang, 2024)
Abstract: Global diversity plays a key role in 21st century education, emphasizing the integration of technology and four key skills: communication, collaboration, critical thinking, and creativity. This article examines the internalization of the value of global diversity in the history of the Ancient Mataram Kingdom, especially the Sanjaya Dynasty and the Syailendra Dynasty. Through a diversity-based history learning approach, students are invited to understand and internalize the values of global diversity. The discovery learning method is used to facilitate students in thinking critically and exploring the values of diversity in historical heritage. The results show that diversity has been an integral part of Indonesian society since the past, providing valuable insights for strengthening diversity in the future